Baseline, enrichment, and ecological risk of arsenic and antimony in the Jiaozhou Bay, a semi-enclosed bay of the Yellow Sea, China. (July 2021) - Gu, Xiang; Lin, Chunye; Xin, Ming; Ouyang, Wei; He, Mengchang; Liu, Xitao; Wang, Baodong; Lian, Maoshan; Lu, Shuang
Abstract: Arsenic (As) and antimony (Sb) are toxic metalloids widely distributed in coastal sediments, but are seldom studied for their geochemical baselines. In this study, sediment samples were collected from Jiaozhou Bay (JZB) to evaluate their baselines, contamination, and ecological risk. Results showed that the As and Sb concentrations were between 3.15 and 11.94 mg/kg and 0.20–0.61 mg/kg, respectively. Sc and Fe showed good performance in developing geochemical baseline functions for the metalloids. Organic matter content and clay had significant positive correlations with metalloid abundance in sediments ( p < 0.01). In the JZB, As and Sb were not enriched in the sediments, with the enrichment factors below 1. Furthermore, the contamination degrees of As and Sb were low in the JZB. In addition, the ecological risks of As and Sb were relatively low in the JZB, with the risk index between 4.02 and 12.70 and 1.68–5.09, respectively. Highlights: Geochemical baseline functions of As and Sb were developed in a semi-enclosed bay. Organic matter and clay were significantly relevant with metalloids in sediments. As and Sb were not enriched in the sediments of the JZB. The contamination degrees and risk levels of As and Sb were low in the JZB.